The Benefit of Papaya Fruit to Fluidity of Breastfeeding in Post Partum Woman - Tondi Rosalinda Sinaga (Jurnal Penelitian Perawat Profesional, 2020)
Papaya or Carica papaya is a fruit that has a galactogogue components such as alkaloids, polyphenols, steroids, flavonoids, and other chemical compounds that serve to increase the production of breast milk. These compounds affect the oxytocin and prolactine hormones to stimulate the mammary gland to secrete breast milk. The objective of this literature review to know the benefits of papaya fruit in the process of breastfeeding in post partum woman. The library sources used are from 28 NCBI articles, Google Scholar, and websites, and used only 22 articles from 2000 up to 2020 . The keywords used are galactagogue, oxytocin, papaya, production of breast milk, prolactine. The method of analysis used is systematic literature review by collecting, evaluating, and developing research on a specific topic focus. The result of the synthesis of several articles that have been found shows that papaya fruit can increase secretes and production of breast milk in breastfeeding process of post partum woman with galactagogue of the fruit.